Self-harm following release from prison: A prospective data linkage study - Borschmann, R.; Thomas, E.; Moran, P.; Carroll, M.; Heffernan, E.; Spittal, M.; Sutherland, G.; Alati, Rosa; Kinner, S. (Sage Publications Ltd., 2017)
© The Royal Australian and New Zealand College of Psychiatrists. Objective: Prisoners are at increased risk of both self-harm and suicide compared with the general population, and the risk of suicide after release from prison is three times greater than for those still incarcerated. However, surprisingly little is known about the incidence of self-harm following release from prison. We aimed to determine the incidence of, identify risk factors for and characterise emergency department presentations resulting from self-harm in adults after release from prison. Method: Cohort study of 1325 adults interviewed prior to release from prison, linked prospectively with State correctional and emergency department records. Data from all emergency department presentations resulting from self-harm were secondarily coded to characterise these presentations. We used negative binomial regression to identify independent predictors of such presentations. Results: During 3192 person-years of follow-up (median 2.6 years per participant), there were 3755 emergency department presentations. In all, 83 (6.4%) participants presented due to self-harm, accounting for 165 (4.4%) presentations. The crude incidence rates of self-harm for males and females were 49.2 (95% confidence interval: [41.2, 58.7]) and 60.5 (95% confidence interval: [44.9, 81.6]) per 1000 person-years, respectively. Presenting due to self-harm was associated with being Indigenous (incidence rate ratio: 2.01; 95% confidence interval: [1.11, 3.62]), having a lifetime history of a mental disorder (incidence rate ratio: 2.13; 95% confidence interval: [1.19, 3.82]), having previously been hospitalised for psychiatric treatment (incidence rate ratio: 2.68; 95% confidence interval: [1.40, 5.14]) and having previously presented due to self-harm (incidence rate ratio: 3.91; 95% confidence interval: [1.85, 8.30]). Conclusion: Following release from prison, one in 15 ex-prisoners presented to an emergency department due to self-harm, within an average of 2.6 years of release. Demographic and mental health variables help to identify at-risk groups, and such presentations could provide opportunities for suicide prevention in this population. Transition from prison to the community is challenging, particularly for those with a history of mental disorder; mental health support during and after release may reduce the risk of adverse outcomes, including self-harm.